2013
DOI: 10.1259/bjr.20130273
|View full text |Cite
|
Sign up to set email alerts
|

The impact of saddle embolism on the major adverse event rate of patients with non-high-risk pulmonary embolism

Abstract: Objective: Wider application of CT angiography (CTA) improves the diagnosis of acute pulmonary embolism (PE). It also permits the visualisation of saddle embolism (SE), namely thrombi, which are located at the bifurcation of the main pulmonary artery. The aim of this study was to assess the prevalence of SE and whether SE predicts a complicated clinical course in patients with non-high-risk PE. Methods: In total, 297 consecutive patients with non-highrisk PE confirmed using CTA in the emergency department were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
8
3
0
Order By: Relevance
“…Patients with a CT RV/LV ratio >1.5 would be more likely to have impaired LV stroke volume, as a consequence of ventricular interdependence, and be farther along the pathophysiologic spiral towards shock [ 32 ]. Additionally, the presence of central clot on CT pulmonary angiogram was found to be a significant predictor of adverse PE outcomes in both the univariable and multivariable model, which is consistent with prior studies [ 28 , 33 ]. Currently used prediction scores do not include the presence of central pulmonary clot as a risk factor [ 7 , 17 ].…”
Section: Discussionsupporting
confidence: 89%
“…Patients with a CT RV/LV ratio >1.5 would be more likely to have impaired LV stroke volume, as a consequence of ventricular interdependence, and be farther along the pathophysiologic spiral towards shock [ 32 ]. Additionally, the presence of central clot on CT pulmonary angiogram was found to be a significant predictor of adverse PE outcomes in both the univariable and multivariable model, which is consistent with prior studies [ 28 , 33 ]. Currently used prediction scores do not include the presence of central pulmonary clot as a risk factor [ 7 , 17 ].…”
Section: Discussionsupporting
confidence: 89%
“…original finding in patients with cancer that emphasises the clinical-radiological dissociation previously described in isolated case reports [ 36,37 ]. Similarly to our results, many of the studies regarding saddle PE in the general population found no difference in overall mortality between saddle and non-saddle PE at 30 days [ 35,[39][40][41][42] ] although data from other heterogenous uncontrolled observational studies [ 43,44 ] suggest a greater risk of in-hospital mortality in patients with saddle PE. Taking all of this into account, the prognostic impact of saddle PE remains inconclusive.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…[ 6 , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] ] Patients with massive PE or PEACE often present with proximal pulmonary artery thrombus, right heart strain (RHS), shock index ≥1 (heart-rate/blood pressure), and troponin elevation. [ 11 , 19 , 20 ] Many PE prognostic models include age, chronic cardiopulmonary disease, or cancer; however, other VTE risks could be associated with PEACE. [ [21] , [22] , [23] , [24] ] Identifying such risks may have diagnostic and prognostic implications for clinicians involved in the evaluation of acute PE and may aid in prognostic modeling.…”
Section: Introductionmentioning
confidence: 99%